Iowa RBA, November 15-20, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Four emails of Iowa RBA updates for November 15-20, 1999. Highlights of the updates include sightings of two White-winged Crossbills, Red-throated Loon, Black-headed Gull, Lesser Black-backed Gull, Pacific Loon, and a Surf Scoter. Epson - sheet feed/flatbed